Quality of life and place attachment among people with severe mental illness. (March 2015) - Marcheschi, Elizabeth; Laike, Thorbjörn; Brunt, David; Hansson, Lars; Johansson, Maria
Abstract: This study investigated the extent to which perceived physical and social-environment qualities of supported housing facilities (SHF) account for variations in the perceived quality of life of people with severe mental illness (SMI). Based on a user-centered approach, people with SMI (N = 72) appraised the environment of their SHF (N = 20). Moreover, it investigated whether place attachment played a role in the relationship established between the environment of SHF and users' quality of life. Perceived physical and social-environment qualities predicted quality of life. Together the two factors accounted for approximately 32% of quality of life variance. Furthermore, attachment to place mediated this relationship. Implications for future planning of psychologically supportive facilities for this vulnerable group in society are discussed. Highlights: The influence of supported housing on the well-being of the mentally ill was tested. Physical and social environment qualities affect the well-being of the mentally ill. Place attachment mediates the effect of the environment on their well-being.